Uncovering novel polyhydroxyalkanoate biosynthesis genes and unique pathway in yeast hanseniaspora valbyensis for sustainable bioplastic production - Desouky A.M. Abd-El-Haleem; Marwa R. Elkatory; Gadallah M. Abu-Elreesh (Scientific Reports)
Abstract This study delves into the exploration of polyhydroxyalkanoate (PHA) biosynthesis genes within wild-type yeast strains, spotlighting the exceptional capabilities of isolate DMG-2. Through meticulous screening, DMG-2 emerged as a standout candidate, showcasing vivid red fluorescence indicative of prolific intracellular PHA granules. Characterization via FTIR spectroscopy unveiled a diverse biopolymer composition within DMG-2, featuring distinct functional groups associated with PHA and polyphosphate. Phylogenetic analysis placed DMG-2 within the Hanseniaspora valbyensis NRRL Y-1626 group, highlighting its distinct taxonomic classification. Subsequent investigation into DMG-2’s PHA biosynthesis genes yielded promising outcomes, with successful cloning and efficient PHA accumulation confirmed in transgenic E. coli cells. Protein analysis of ORF1 revealed its involvement in sugar metabolism, supported by its cellular localization and identification of functional motifs. Genomic analysis revealed regulatory elements within ORF1, shedding light on potential splice junctions and transcriptional networks influencing PHA synthesis pathways. Spectroscopic analysis of the biopolymer extracted from transgenic E. coli DMG2-1 provided insights into its co-polymer nature, comprising segments of PHB, PHV, and polyphosphate. GC-MS analysis further elucidated the intricate molecular architecture of the polymer. In conclusion, this study represents a pioneering endeavor in exploring PHA biosynthesis genes within yeast cells, with isolate DMG-2 demonstrating remarkable potential. The findings offer valuable insights for advancing sustainable bioplastic production and hold significant implications for biotechnological applications.